(3JTQjM GdYjfs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3Ef GdYjf eQcHI ef SHY WHbGJ hKdGK QWhHGJ , CeG HjGf GdWHbGJ aEf GdYUHI GdeLhaI EPG GfMOQJ Edi GdYjf s
(3BNQgG (B:s
(3hefaYI GdQWhHI GdHjVjI JQWjH GdLdjOjI dJHbi Ydi UaGFgG hgPg UhQI GdYjf hGdYUHjI GdMGSI ef GdOeGZ s
(3Vef eLehY s
(3GfXQg eY OaY GdSehe (B" (3Qbe (B" 467"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKfi (B- (3U (B56 s
Keywords: (3GdWHs